Serum and lymph pharmacokinetics of nilotinib delivered by yeast glucan particles per os - Šalamúnová, Petra; Krejčí, Tereza; Ryšánek, Pavel; Saloň, Ivan; Kroupová, Jiřina; Hubatová-Vacková, Anna; Petřík, Jakub; Grus, Tomáš; Lukáč, Peter; Kozlík, Petr; Křížek, Tomáš; Dammer, Ondřej; et al. (International journal of pharmaceutics, 2023)
Nilotinib is a selective tyrosine-kinase inhibitor approved for the treatment of chronic myeloid leukemia. It is poorly soluble in aqueous media and has a low oral bioavailability. Nilotinib encapsulation into yeast glucan particles (GPs) was investigated in this work as a means of increasing bioavailability. The amorphization of nilotinib in GPs resulted in an increased dissolution rate, which was confirmed by in vitro experiments using biorelevant dissolution media. Simultaneously, GPs containing nilotinib were effectively taken up by macrophages, which was quantified in vitro on cell cultures. The overall oral bioavailability in a rat model was approximately 39 % for nilotinib delivered in a reference formulation (Tasigna) and was almost doubled when delivered in GPs. The contribution of glucan particles to the lymphatic transport of nilotinib was quantified. When delivered by GPs, cumulative nilotinib absorption via the lymphatic system increased by a factor of 10.8 compared to the reference, but still represented arelative bioavailability of only 1.12 %. The cumulative uptake of GPs in the lymph was found to be 0.54 mg after a single dose of 50 mg. Yeast glucan particles can therefore serve as a drug delivery vehicle with a dual function: dissolution rate enhancement by amorphization, and, to asmaller extent, lymphatic delivery due to macrophage uptake.
Keywords: krysa rodu Rattus; Saccharomyces cerevisiae; Animals; Glucans; Administration, Oral; zvířata; pyrimidiny; glukany; aplikace orální; Rats; Pyrimidines